2020
DOI: 10.1186/s12940-020-0568-1
|View full text |Cite
|
Sign up to set email alerts
|

Lung function and systemic inflammation associated with short-term air pollution exposure in chronic obstructive pulmonary disease patients in Beijing, China

Abstract: Background: Exposure to air pollution is associated with chronic obstructive pulmonary disease (COPD). However, findings on the effects of air pollution on lung function and systemic inflammation in Chinese COPD patients are inconsistent and scarce. This study aims to evaluate the effects of ambient air pollution on lung function parameters and serum cytokine levels in a COPD cohort in Beijing, China. Methods: We enrolled COPD participants on a rolling basis from December 2015 to September 2017 in Beijing, Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 39 publications
(41 reference statements)
7
63
2
Order By: Relevance
“…Notably, LPS/1,4-CQ protocol on FcgRIIb −/− mice was a stimulation upon an active inflammation (environmental toxins exposure during inflammation). These data also support the enhanced adverse effects of air pollutants (containing Ahr stimulator) in patients with ongoing active respiratory inflammation [71][72][73]. Although a short-term Ahr stimulation (without LPS) did not induce inflammation, a long-term Ahr stimulation increased serum cytokines in FcgRIIb −/− mice but not in WT mice.…”
Section: The Enhanced Activity Of Lupus-like Condition Through the Aryl Hydrocarbon Receptor Activation A Possible Impact Of The Environmsupporting
confidence: 67%
See 1 more Smart Citation
“…Notably, LPS/1,4-CQ protocol on FcgRIIb −/− mice was a stimulation upon an active inflammation (environmental toxins exposure during inflammation). These data also support the enhanced adverse effects of air pollutants (containing Ahr stimulator) in patients with ongoing active respiratory inflammation [71][72][73]. Although a short-term Ahr stimulation (without LPS) did not induce inflammation, a long-term Ahr stimulation increased serum cytokines in FcgRIIb −/− mice but not in WT mice.…”
Section: The Enhanced Activity Of Lupus-like Condition Through the Aryl Hydrocarbon Receptor Activation A Possible Impact Of The Environmsupporting
confidence: 67%
“…For example, Ahr agonist of the particulate matter (PM) in air pollution (a hydrocarbon main structure) might be less toxic to the patients but the other attached components (heavy metals, nitrate, sulfate, and ammonium) might be a main cause of toxicity [ 14 , 69 , 70 ]. Because of the possible spontaneous endotoxemia in patients with lupus [ 34 , 46 ], our data implied an impact of the condition that initiate inflammation, especially leaky-gut-induced endotoxemia, in a lupus-like condition before the stimulation by environmental toxins [ 71 , 72 , 73 ]. The avoidance of endotoxemia should also be considered in patients with lupus.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the expression of lnc‐PVT1 is gradually increased with the elevation of cardiac function classification, and is positively correlated with collagen I and collagen III (two major proteins contributing to atrial fibrosis) in AF patients 20 ; its SNP is positively associated with GOLD stage, FVC, FEV 1 , and diffusing capacity of carbon monoxide in COPD smoker patients 8 . In this study, we observed that lnc‐PVT1 expression was positively correlated with GOLD stage and inflammatory cytokine levels (TNF‐α, IL‐6, IL‐8, and IL‐17, which are well known as pro‐inflammatory cytokines in COPD 22,23 ) in both AECOPD patients and stable COPD patients, which might be explained as follows: (a) upregulated lnc‐PVT1 might make the ASM cells in an over‐activated state via promoting the viability, proliferation, and migration of ASM cells, resulting in airway narrowing (due to the contractile properties of ASM cells) and further enhanced airflow obstruction; therefore, lnc‐PVT1 expression was positively correlated with GOLD stage in AECOPD patients and stable COPD patients 17 ; and (b) lnc‐PVT1 might promote inflammatory responses via activating MAPK/NF‐κB pathway or via sponging its certain targeted miRNAs, thereby facilitated the production and release of inflammatory cytokines, and lnc‐PVT1 expression was positively associated with inflammation level in AECOPD patients and stable COPD patients 6,17,18 …”
Section: Discussionmentioning
confidence: 50%
“…8,20 For example, the expression of lnc-PVT1 is gradually increased with the elevation of cardiac function classification, and is positively correlated with collagen I and collagen III (two major proteins contributing to atrial fibrosis) in AF patients 20 ; its SNP is positively associated with GOLD stage, FVC, FEV 1 , and diffusing capacity of carbon monoxide in COPD smoker patients. 8 In this study, we observed that lnc-PVT1 expression was positively correlated with GOLD stage and inflammatory cytokine levels (TNF-α, IL-6, IL-8, and IL-17, which are well known as pro-inflammatory cytokines in COPD 22,23 ) in both AECOPD patients and stable COPD patients, which might be ex- COPD patients. 6,17,18 As one of the frequently investigated miRNAs, miR-146a is reported to take a crucial role in chronic airway respiratory diseases.…”
Section: Discussionmentioning
confidence: 69%
“…NO 2 and SO 2 have been observed to potentiate adverse health consequences including increased all-cause mortality (Burnett et al 2004 ; Stieb et al 2002 ; Yorifuji et al 2019 ) and exacerbation of asthma (Park et al 2001 ; Andersson et al 2006 ; Sunyer et al 2002 ). While NO 2 exposure has been linked to aggravation of COPD (Lamichhane et al 2018 ; Gao et al 2020 ; Zhang et al 2018 ) and cardiovascular mortality (Bourdrel et al 2017 ; Faustini et al 2014 ; Mills et al 2015 ), this association remains unclear for SO 2 exposure. Long-term impacts of SO 2 have been associated with respiratory mortality (Atkinson et al 2016 ) and increased risk of developing lung cancer (Lee et al 2002 ).…”
Section: Sex Differences In the Response To Nitrogen Dioxide And Sulfmentioning
confidence: 99%